Subthalamic nucleus lesions: widespread effects on changes in gene expression induced by nigrostriatal dopamine depletion in rats - Delfs, JM (J Neurosci, 1995)
Lesions of the subthalamic nucleus block behavioral effects of nigrostriatal dopamine depletion in rats and primates, but the contribution of this region to the molecular effects of dopaminergic lesions is unknown. The effects of subthalamic nucleus lesions alone or in combination with a 6-hydroxydopamine-induced lesion of the substantia nigra were examined in adult rats. Unilateral subthalamic nucleus lesions caused ipsiversive rotation after peripheral administration of apomorphine and a small decrease in glutamic acid decarboxylase (GAD) mRNA in the ipsilateral globus pallidus (external pallidum). Confirming previous results, nigrostriatal dopaminergic lesions caused contraversive rotation after apomorphine injection, and increased enkephalin mRNA in the striatum, GAD mRNA in the globus pallidus, and somatostatin mRNA in the entopeduncular nucleus (internal pallidum) ipsilateral to the lesion. In addition, the lesion decreased substance P mRNA in the ipsilateral striatum compared to the contralateral side, and GAD mRNA in the contralateral entopeduncular nucleus. These effects were abolished in rats with lesions of the subthalamic nucleus and substantia nigra on the same side. Thus, the subthalamic lesions prevented changes in gene expression induced by dopamine depletion, not only in regions receiving a direct input from the subthalamic nucleus (ipsilateral pallidum), but also in regions which do not (striatum and contralateral pallidum). This suggests that polysynaptic pathways regulated by the subthalamic nucleus contribute to the effects of dopaminergic lesions in many regions of the basal ganglia. This pivotal role of the subthalamic nucleus may account for the beneficial effects of subthalamic nucleus lesions on motor symptoms resulting from dopamine depletion.